Black hole quantum mechanics in the presence of species. Issue 7 (23rd April 2013) - Dvali, G.; Gomez, C.; Lüst, D.
Abstract: Recently within the context of a microscopic quantum theory, the Black Hole's Quantum N‐Portrait, it was shown that continuous global symmetries are compatible with quantum black hole physics. In the present paper we revise within the same framework the semi‐classical black hole bound on the number of particle species N species . We show that unlike the bound on global charge, the bound on species survives in the quantum picture and gives rise to a new fundamental length‐scale, L species = √( N species ) L P, beyond which the resolution of species identities is impossible. This finding nullifies the so‐called species problem. This scale sets the size of the lightest quantum black hole in the theory, Planckion . A crucial difference between the gravitational and non‐gravitational species emerges. For gravitational species, the lightest black holes are exactly at the scale of perturbative unitarity violation, which is a strong indication for self‐UV‐completion of gravity. However, non‐gravitational species create a gap between the perturbative unitarity scale and the lightest black holes, which must be filled by some unitarity‐restoring physics. Thus, self‐UV‐completion of gravity implies that the number of non‐gravitational species must not exceed the gravitational ones. Abstract : Within the framework as used in the preceeding paper the semi‐classical black hole bound on the number of particle species Nspecies is revised. It is shown that unlike the bound on global charge, the bound on species survives in the quantum picture and gives rise to a new fundamental length‐scale, beyond which the resolution of species identities is impossible. This finding nullifies the so‐called species problem. This scale sets the size of the lightest quantum black hole in the theory, the Planckion.